ACQUIRING TECHNICAL COMPETENCY CERTIFICATION FOR ENHANCED SOCIAL SECURITY IN ORGANIZATIONS: THE INFLUENCING FACTORS (Social Security Management Journal, 2024)
Technically competent employees are important to ensure social security issues in organizations can be addressed effectively. However, motivating employees to acquire technical certification is not easy. This study examines the financial gains, job security, status, and opportunities to advance, advisory received and financial assistance, age, position category and income level factors on technical employees’ intention to acquire technical certification. A survey was conducted among TNB Genco Technical Service staff, involving a sample of 215 respondents. The findings indicated that only age and position category affect employees’ intention to acquire technical certification. Thus, organizations should take note of these factors when revising career development policies.